2020
DOI: 10.1089/bfm.2019.0220
|View full text |Cite
|
Sign up to set email alerts
|

Baby-Friendly Hospital Initiative Is Associated with Lower Rates of Neonatal Hyperbilirubinemia

Abstract: Background: The Baby-Friendly Hospital Initiative (BFHI) advances practices that support exclusive breastfeeding. BFHI practices are associated with increased breastfeeding rates, however, other patient outcomes are not well described. This study examined the association of BFHI practices with hyperbilirubinemia and phototherapy between groups of newborns born before and after BFHI implementation at an urban, tertiary academic medical center in South Carolina. Materials and Methods: We conducted a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…[4][5][6] Also, in a study of Hudson et al they found that implementation of baby-friendly hospital initiative for breastfeeding in a single hospital center was significantly associated with reduced rates of neonatal hyperbilirubinemia and phototherapy treatment among newborns, without increased rates of 30-day hospital readmissions for the treatment of hyperbilirubinemia. [24] In our study, we found that the formula was the first prelacteal feed in babies who received phototheraphy treatment >24 hours period. Also, statistical significance was achived between the two groups for first prelacteal feed.…”
Section: Discussionmentioning
confidence: 61%
“…[4][5][6] Also, in a study of Hudson et al they found that implementation of baby-friendly hospital initiative for breastfeeding in a single hospital center was significantly associated with reduced rates of neonatal hyperbilirubinemia and phototherapy treatment among newborns, without increased rates of 30-day hospital readmissions for the treatment of hyperbilirubinemia. [24] In our study, we found that the formula was the first prelacteal feed in babies who received phototheraphy treatment >24 hours period. Also, statistical significance was achived between the two groups for first prelacteal feed.…”
Section: Discussionmentioning
confidence: 61%
“…Our analysis showed a modest increase in all-cause 30-day readmissions following BFHI. Hudson and colleagues have previously shown a reduction in hyperbilirubinemia without any change in readmission for hyperbilirubinemia following BFHI in a single center [ 17 ]. A study from a single center in the West Indies showed an increase in admission for hypernatremic dehydration following BFHI [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true in South-East Asian communities with higher rates due to a genetic predisposition to glucose-6-phosphate dehydrogenase deficiency. Strengthening breastfeeding support to prevent breastfeeding jaundice, 5 and optimising NNJ management, will maximise the benefits of breastfeeding promotion. Lai Ling Hui…”
Section: Reducing Admissions For Neonatal Jaundice Are Needed To Maxi...mentioning
confidence: 99%